Peran Karyawan Dalam Meningkatkan Layanan Digitalisasi Pada Nasabah Bank BCA Undaan Surabaya - Setijadi, Harmony Jordan Miracle; Fadhillah, Is (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study was prepared by the author to determine the implementation of the role and efforts of employees in improving digitalization services that have an impact on customer response at Bank BCA Undaan Surabaya. The background of this research is the development of BCA Bank's transaction service system which has adapted to digitalization services. In his research, the author used qualitative methods, with customers as subjects and employees as objects. The data obtained are the results of observations and interviews. The results obtained from this research are: 1) The role of Bank BCA Undaan Surabaya employees is crucial because in addition to acting as a liaison between technology and customers, employees also provide education and assistance to customers and ensure the resolution of obstacles; 2) The response of customers to the digitalization services of Bank BCA Undaan Surabaya is mostly welcoming because it improves transactions to be efficient and practical; 3) Efforts made by employees in improving digitalization services to customers include a proactive approach, internal collaboration, and friendly and responsive service. It can be concluded that the proper implementation of employee roles and efforts can have a good impact on customer response in using digitalization services.